UMP volunteers work together to clean houses due to flood - Mimi Rabita, Abdul Wahit (2021)
MARAN, 5 January 2021 - The flood that began to recede in Maran, Pahang offered opportunities for Universiti Malaysia Pahang (UMP) volunteers to help clean the flood-ravaged house of a university staff soaked with mud, besides damaged goods and furniture.